Produção de uma sequência didática com jogos lúdicos para o ensino de genética no ensino médio - Borges, Elisvan Vieira (2021)
It is clear that some terms of genetics, such as phenotype, homologous chromosomes, heterozygote, dominant alleles, among others, are difficult for students to understand. Thus, in order for there to be greater interest and understanding of the concepts covered in Biology, the teacher must promote different methodologies in addition to the expository and dialogued classes, so that it promotes the protagonism and the cognitive skills of the students. Thus, the objective of this study was to develop a didactic sequence using games as a facilitating tool for teaching and learning the basic concepts in genetics. This research took place in the year 2019 with a class of the 3rd grade of integral high school, consisting of 22 students, in a state public school in the municipality of Esperança-PB. For this report of didactic intervention that fits in the action research, using as a scientific method the qualitative and quantitative approach of the results through the use of questionnaires, participant observation and bibliographic review, 27 classes of 50 minutes were used. One week after the execution of the lectures and dialogues, a pre-test questionnaire with objective and discursive questions was applied to the students. The result revealed that among the research participants, traditional classes were not enough to guarantee students' understanding of basic concepts in genetics. In another stage, the room was divided into five groups, and each received an investigative script to guide the making of playful games. In this phase, the teacher acted as a mediator and the students as protagonists, through readings, research, discussion, creativity and interaction. Thus, five games were produced: Memorizando Genética; Show of Genetics, Playful Genetics, Mix of Genetics and Genetic trail with description and rules. Each team presented their game, followed by a moment of interaction with the class. In the final phase, a perception questionnaire was applied via the Google platform, which showed the acceptance of students for this activity, and a better performance in learning. As a product of this work, a Didactic Sequence of an investigative nature was elaborated using the production of games as a didactic strategy, which can be used and adapted for teachers of Biology and other areas. It is concluded that the use of games in the classroom was extremely relevant, since, through this playful practice it was possible to stimulate communication, argumentation and problem solving, within the classroom, as well as, the protagonism and the cognitive capacity of the students were encouraged.